Pengaruh Brain Based Learning Terhadap Keterampilan Berpikir Kritis Dan Hasil Belajar Siswa SMA Negeri 9 Palu Pada Materi Larutan Asam Basa - Irma Irma; Suherman Suherman; Solfarina Solfarina (Universitas Tadulako, 2015)
This research is about influence of brain based learning (BBL) toward critical thinking skill and student’s learning achievement at grade XI IPA SMA Negeri 9 Palu in acid base solution concept. The method is quasy experiment with design of pretest-posttest control group design. The technic of analysis used nonparametric statistical method mann whitney U-test. The sample of this research was class XI IPA 1 as experiment group and class XI IPA 3 as control, which choosen by purposive sampling technic. Analysed found, sig.2-tailed (0,000) < 0,05 has significant difference of critical thinking skill, learning achievement of experiment and control gruop. Result of Test <g> were improved of critical thinking skill and student’s learning achievement in experiment group more high than control group. The conclusion of this research was brain based learning (BBL) has influential to improved critical thinking skill, student’s learning skill at grade XI IPA SMA Negeri 9 Palu in acid base solution concept.